Two decades of public sector innovation: building an analytical framew ork from a systematic literature review of types, strategies, conditio ns, and results - Criado, J. Ignacio; Alcaide-Muñoz, Laura; Liarte, Irene (Public Management Review, 2023)
Scholarly attention in innovation in the public sector is growing rapi dly, provoking analytical complexity. We developed a systematic litera ture review about Public Sector Innovation (PSI), analysing 169 articl es published between 2001 and 2021, using PRISMA. We present a compreh ensive approach to PSI testing and empirically develop an analytical f ramework based on the most common combinations of the studied dimensio ns. Additionally, we propose three main research avenues for the futur e of PSI: (1) studying PSI in different contexts, (2) expanding the an alysis of configurations in PSI initiatives, and (3) analysing ambidex trous strategies to support the practical implementation of PSI.